2007
DOI: 10.4081/ijas.2007.1s.469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of period of milk production and ripening on quality traits of Asiago cheese

Abstract: After 6 and 12 months of ripening, samples of Asiago d’Allevo were analyzed for quality traits. Cheeses were produced during 3 periods using milk from cows fed a total mixed ration (TMR, May) or grazing on alpine pasture (AG) in early (July) and late (Sept.) summer. Data were submitted to ANOVA considering ripening, milk production period and farm as main effects, and whole cheese weight as covariate. During ripening, pH of AGcheese was significantly lower than that of TMR-cheese; crude fat and protein signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 2 publications
2
9
0
1
Order By: Relevance
“…Unsurprisingly, neither farm nor management system affected cheese color. Previous studies reported changes in cheese instrumental color as a consequence of using fresh forage and the closely related β-carotene content [ 31 , 39 , 40 , 41 ]. However, β-carotene is not detectable in ewes’ milk due to its enzyme-catalyzed cleavage to retinal in the sheep liver [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unsurprisingly, neither farm nor management system affected cheese color. Previous studies reported changes in cheese instrumental color as a consequence of using fresh forage and the closely related β-carotene content [ 31 , 39 , 40 , 41 ]. However, β-carotene is not detectable in ewes’ milk due to its enzyme-catalyzed cleavage to retinal in the sheep liver [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Asiago d'Allevo samples were manufactured with raw, partially skimmed milk in a commercial dairy plant in the case A and in an artisanal dairy plant belonging to the farm (in situ) in the cases B and C. Cheese-making procedure following the Italian official protocol included the use of starter culture (a mixture of Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus) and rennet (see Segato et al 2007 andLignitto et al 2010 for more details). According to a 3×3 experimental design, the sampling scheme adopted considered three cheese production systems (A, B, and C) and three lengths of ripening time: 6, 12, or 18 months.…”
Section: Cheese Sampling and Cheese-making Proceduresmentioning
confidence: 99%
“…Cheese authentication is a hot topic of interest for producers, consumers and policy makers, with a specific focus to control the labelling claims on high-quality dairy products. Indeed, these products and the Protected Designation of Origin (PDO) ones in particular have distinctive characteristics according to their geographical production area, cows management and feeding system as well as to cheese making procedure [1,2,3].…”
Section: Introductionmentioning
confidence: 99%